2021
DOI: 10.3390/ijms22073506
|View full text |Cite
|
Sign up to set email alerts
|

Jasmonic Acid Pathway in Plants 2.0

Abstract: The plant hormone jasmonic acid (JA) and its derivative, an amino acid conjugate of JA (jasmonoyl isoleucine: JA-Ile), are signaling compounds involved in the regulation of cellular defense and development in plants [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Contrarily, JA was much more bioactive than indole-3-carbaldehyde and 3-ICA against Bgt E21, and the disease severity of Bgt E21 decreased significantly with the concentration increase of JA treatment ( Table 2 ). In plants, the plant hormone JA and its derivatives are involved in regulating a diverse set of processes including cellular development, defense, and resistance to both abiotic and biotic stress ( Ruan et al., 2019 ; Gomi, 2021 ). For instance, when applied to plants, the JA-derivative lasiojasmonate A (LasA), isolated from Lasiodiplodia mediterranea , a pathogen of grapes, induces many JA-regulated response in planta at both the genetic and physical level ( Chini et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Contrarily, JA was much more bioactive than indole-3-carbaldehyde and 3-ICA against Bgt E21, and the disease severity of Bgt E21 decreased significantly with the concentration increase of JA treatment ( Table 2 ). In plants, the plant hormone JA and its derivatives are involved in regulating a diverse set of processes including cellular development, defense, and resistance to both abiotic and biotic stress ( Ruan et al., 2019 ; Gomi, 2021 ). For instance, when applied to plants, the JA-derivative lasiojasmonate A (LasA), isolated from Lasiodiplodia mediterranea , a pathogen of grapes, induces many JA-regulated response in planta at both the genetic and physical level ( Chini et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that MeJA can promote terpene biosynthesis in plants and is involved in the stomatal closure of cucumbers [ 11 ]. Furthermore, relevant studies have shown that MeJA can regulate the respiratory metabolism, carotenoid synthesis, ethylene synthesis, phenylpropane metabolism, and anthocyanin metabolism of fruit and vegetable products.…”
Section: Jasmonic Acid (Ja)mentioning
confidence: 99%
“…MeJAresponsive element is the most abundant element, containing 350 instances. As we all know, Methyl jasmonic acid regulates physiological processes such as plant growth and development, especially the response of plants to biotic and abiotic stresses [30]. DnMYB23 contained 24 MeJA-responsive elements in its 2-k upstream regulatory region.…”
Section: Prediction Of Cis-acting Elements In the Promoters Of 125 Dn...mentioning
confidence: 99%